Pengaruh Model Pembelajaran Kooperatif Tipe Team Games Tournament (TGT) Terhadap Hasil Belajar IPS Siswa Kelas VII Di MTs Negeri 1 Rokan Hulu (Bakoba : Journal of Social Science Education, 2024)
The background to this research is that the low social studies learning outcomes of students at MTs Negeri 1 Rokan Hulu are caused by the conventional learning model (lecture). The aim of this research is to determine the influence of the Team Games Tournament (TGT) type cooperative learning model on social studies learning outcomes for class VII students at MTs Negeri 1 Rokan Hulu. The method used in this research is a quasi-experimental method. The population in this study were all class VII students, totaling 126 students. The sample in this research was students in class VII.B and VII.D, totaling 63 students. The results of this study show that the pre-test and post-test value data are normally distributed and the variance is homogeneous. The average pre-test score for the experimental class was 38.41 and the control class 38.68. The average post-test score for the experimental class was 73.35 and the control class was 50.46. The research results were calculated using t-test formula with the results t_count > t_table = 7.209 > 1.670, which means that there is an influence of the Team Games Tournament (TGT) Type Cooperative Learning Model on the Social Sciences Learning Outcomes of Class VII Students at MTs Negeri 1 Rokan Hulu. The suggestions in this research are for schools. The Team Games Tournament type cooperative learning model can be used as valuable information for schools, because schools can implement models, learning methods and effective learning strategies that can improve student learning outcomes. Keywords: Learning Outcomes, Team Games Tournament (TGT) Learning Model, Social Science.